Cloning and disruption of the antigenic catalase gene of Aspergillus fumigatus. - Calera, J A (1997)
Aspergillus fumigatus possesses two catalases (described as fast and slow on the basis of their electrophoretic mobility). The slow catalase has been recognized as a diagnostic antigen for aspergillosis in immunocompetent patients. The antigenic catalase has been purified. The enzyme is a tetrameric protein composed of 90-kDa subunits. The corresponding cat1 gene was cloned, and sequencing data show that the cat1 gene codes for a 728-amino-acid polypeptide. A recombinant protein expressed in Pichia pastoris is enzymatically active and has biochemical and antigenic properties that are similar to those of the wild-type catalase. Molecular experiments reveal that CAT1 contains a signal peptide and a propeptide of 15 and 12 amino acid residues, respectively. cat1-disrupted mutants that were unable to produce the slow catalase were as sensitive to H2O2 and polymorphonuclear cells as the wild-type strain. In addition, there was no difference in pathogenicity between the cat1 mutant and its parental cat1+ strain in a murine model of aspergillosis.